Digilantism Practice: The Online Shaming for the Cheaters - Augustin Chairil; Dian Hutami Rahmawati; Latif Ahmad Fauzan (LPPM Stikosa - AWS, 2023)
Pelakor, or perebut lelaki orang (someone who cheats with their husband) is a term that is very common on the internet, especially on social media such as Facebook. The trend of shaming and viral-ing ‘pelakor’ on social media is an interesting and recurring consumption. The practice of online shaming, and going viral is a practice that is normalized by some social media users. This article wants to explore how online shaming practices are carried out by Anti Pelakor Indonesian facebook groups and discussed with digilantism concept. Netnography is used in this research to see virtual activities occurring in groups. As well as virtual observations during January – June 2019 and interviews with shaming actors to enrich the data. The results of the API Group's observations describe data granulation, ranging from uploads of disclosures of household problems and mistress, viral practices, online shaming, and doxing, to wiretapping the Whatsapp instant messaging application which leads to the practice of spreading privacy. The practice of shaming has some benefits also risks and raises ethical problems.